molecular detection of diarrheagenic escherichia coli pathotypes isolated from children with diarrhea. A cross-sectional study in Mbarara city, South Western Uganda. - Akankunda, Phionah K; Natuhwera, Jemimah; Kirunda, Charles Halidi; Bagenda, Nkubi; San, Umar Mohammed; Bazira, Joel (Student's Journal of Health Research Africa, 2026)
Background Diarrheal diseases remain a global public health concern affecting children, with a high prevalence in resource-limited settings. In many poor nations, diarrheal diseases have been listed as 1 of the top 10 causes of mortality. Objective This study aimed to determine the prevalence and antibiotic susceptibility profiles of diarrheagenic Escherichia coli (E. coli) pathotypes with diarrhea using Polymerase Chain Reaction in Mbarara City. Methodology It was a cross-section hospital-based study where 391 stool samples were collected from children aged six months and 12 years presenting with diarrhea and not taking any antibiotic treatment for diarrhea at the time of the investigation. Results Out of 391 stool samples collected, 78 were positive for E. coli giving an overall prevalence of 19.95 %. Of the 78 (19.95 %) positive samples, males were 18 (54.55%) and females were 25 (55.56%). Among the 78 E. coli isolates still, 43 (55.13 %) were pathogenic and belonged to the three common pathotypes including Enteropathogenic E. coli (EPEC), which was the most prevalent pathotype (86.05 %), followed by Enterohaemorrhagic E.coli (EHEP) (9.30 %), while enter-invasive was the least (4.65%). The E. coli isolates were most sensitive to chloramphenicol, followed by imipenem (70%), tetracycline (30%), ceftriaxone (28%) and amoxicillin (26%) was the most resistant Conclusion Diarrheagenic E. coli (DEC) is prevalent in Mbarara City and is an important agent that should be considered in routine studies and surveillance for childhood acute diarrheal disease. Recommendations Strengthening molecular diagnostic capacity in health laboratories should be supported to adopt molecular diagnostic techniques (e.g., PCR) for routine detection of diarrheagenic E. coli, since conventional culture methods may not differentiate pathogenic E.coli pathotypes.